“Desarrollo del módulo recursos humanos para su integración en el ERP de la empresa SISCOM” - Panchi Moreno, Andy Steveen (2024)
At this company SISCOM S.A provider of internet and telecommunications services, located in San Buenaventura parish, Latacunga canton, the identified problem was the generation of manual role payments, which is inefficient. The main objective is to develop the Human Resources module, using free software with PHP programming language, to integrate it into ERP allowing the management area in the company. Therefore, it was proposed the creation of a Human Resources module, in order to determine the payment to employees accurately. The application process included, drafting of information on methodologies, tools and used techniques. An interview was conducted to identify the needs, for the web application a programming language in PHP, HTML was used to design graphical user interface to contrast CSS styles, CodeIgniter frameworks was applied. To collect information two types of field and bibliographic research were opted, and, XP methodology (Extreme Programming) was implemented to facilitate collaborative work between people, with the iterative delivery of user stories. The system consists of two main actors: the administrator and the manager, each one with different roles. Through this proposal, the courrem problem of implementing an integrated payroll system was solved. This will efficiently cover the needs of the company human resources department.